A MODULAR ALGORITHM FOR THE DYNAMICS OF MULTIPLE FLEXIBLE ROBOTS - Bonaventura, C S; Jablokow, K W; Buffinton, K W (International journal of robotics & automation, 2007)
This paper presents an efficient modular algorithm for the dynamic simulation of systems of multiple flexible robots with multiple concurrent constraints. This research represents an important extension of previous work in the modular dynamic simulation of complex rigid-body systems. In addition to a summary of the algorithm, the treatment of potentially critical nonlinear strain and kinematic effects is also discussed. The algorithm is validated through several examples, including both series and parallel robot configurations. [PUBLICATION ABSTRACT]